Di Balik Layar: Tantangan dan Peluang dalam Mengimplementasikan Pendidikan Petualangan di Organisasi Mahasiswa - Sri Handayani; Rani, Rani; Muhammad Ali Husen (PT. Intelek Cendikiawan Nusantara, 2025)
This research explores the opportunities and challenges in pioneering educator adventure programs within student organizations. In a qualitative approach, using interviews with student organization leaders and program coordinators, observation and document analysis of the adventure program, an attempt was made to understand the complex combination process within the organization in the implementation of adventure-based learning experiences. The findings revealed the consolidation of various challenges such as limited resources, security issues, and even resistance to change. However, the research also identified the crucial presence of significant opportunities for personal development, leadership development and community building. Adventure education has the potential to develop skills such as teamwork, problem-solving and resilience, as well as contribute to raising environmental awareness and developing a deeper connection with nature. This research dedicates itself to providing valuable insights to student organizations and educators seeking to deploy adventure education in their programs, by offering ways to solve challenges and maximize benefits in experiential learning.